Exploring biotic constraints in the biodiesel plant, Pongamia pinnata (L.) Pierre cultivation: A comprehensive review: EXPLORING BIOTIC CONSTRAINTS IN PONGAMIA PINNATA (L.): A COMPREHENSIVE REVIEW - N MUKTA; S HARIHARAN; P DURAIMURUGAN; D NEETHU ROY (Journal of Oilseeds Research, 2024)
Pongamia pinnata, a vital non-edible oilseed tree, hold ssignificant potential for various applications including biodiesel production and traditional medicine due to its high seed yield and resilience to harsh conditions. However, it faces substantial challenges from a multitude of pests and diseases throughout its lifecycle, impacting both seedlings and mature trees. Insects such as termites, white grubs, and caterpillars, as well as fungal pathogens like Ganoderma lucidum and Colletotrichum gloeosporioides, pose substantial threats to P. pinnata cultivation. Additionally, nematodes and pod rot fungi contribute to yield losses and storage issues. Despite these challenges, management strategies, including biological control and chemical pesticides, offer avenues for mitigating pest and disease incidence. Collaborative research and innovation are essential for developing sustainable solutions and enhancing the resilience of P. pinnata plantations. By addressing these challenges collectively, we can unlock the full potential of P. pinnata, supporting biodiversity conservation, ecosystem restoration, and rural livelihoods.